The Effectiveness of Brain Gym Exercise on Students Learning Concentration - Nafiah, Nafiah; Gifari, Muhammad Yusrin Al; Oktaviani, Yulisha Eva (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Concentration disturbances among students are an important issue in higher education, especially in the digital era filled with distractions. This study aims to explore the effectiveness of brain gym exercise Exercise as a non-pharmacological intervention to enhance students' concentration. Methods: The method used is a quasi-experimental design with a pre-test and post-test without a control group, involving 50 students from the D3 Physiotherapy Politeknik Unggulan Kalimantan. Concentration measurements were conducted before and after the intervention using a grid concentration test form. Results: The results show a significant (P<0,05) increase in students' concentration levels. Conclusion: Brain gym exercise can serve as an effective alternative for improving students' concentration, especially when performed regularly and continuously. This study contributes to the development of a holistic approach to addressing concentration disturbances in the academic environment.